Comparison of laparoscopic and open intraoperative ultrasonography for staging liver tumours. Issue 4 (21st January 2013) - Viganò, L.; Ferrero, A.; Amisano, M.; Russolillo, N.; Capussotti, L.
Abstract: Background: Laparoscopic liver surgery must reproduce open surgical steps. Intraoperative ultrasonography (IOUS) is mandatory, but reliability of laparoscopic IOUS has been poorly evaluated. The aim of this study was to compare laparoscopic versus open IOUS in staging liver tumours. Methods: All patients scheduled for liver resection between September 2009 and March 2011 were considered. Inclusion criteria were primary and metastatic tumours. Exclusion criteria were: hilar/gallbladder cholangiocarcinoma, ten or more lesions, repeat resection, laparoscopic hepatectomy, adhesions and unresectability. Following percutaneous ultrasonography and thoracoabdominal computed tomography (CT), and on indication contrast‐enhanced (CE) liver magnetic resonance imaging (MRI) and/or positron emission tomography (PET)–CT, patients were scheduled for laparoscopy, laparoscopic IOUS, then laparotomy, open IOUS and Partial hepatectomy. Data were collected prospectively. Reference standards were final pathology and 6‐month follow‐up results. Results: Sixty‐five patients were included, who had a median of 3 preoperative imaging studies (ultrasonography/CT 100 per cent, CE‐MRI 67 per cent, PET–CT 54 per cent). A total of 119 lesions were diagnosed. Laparoscopic IOUS detected 22 additional lesions (+18·5 per cent) in 14 patients. Open IOUS detected two additional lesions, but did not confirm four lesions; overall 20 additional lesions (+16·8 per cent) were detected in ten patients. Pathology confirmed 14 newly detected malignant nodules (+11·8 per cent) in eight patients. After 6 months ten new nodules were identified in six patients. The sensitivity of preoperative imaging, laparoscopic IOUS and open IOUS was 83·1, 92·3 and 93·0 per cent respectively; accuracy was 79, 82 and 88 per cent. In comparison with open IOUS, the sensitivity and accuracy of laparoscopic IOUS were 98·6 and 94 per cent. Conclusion: Laparoscopic IOUS is a reliable tool for staging liver tumours with a performance similar to that of open IOUS in detecting new nodules. Copyright © 2013 British Journal of Surgery Society Ltd. Published by John Wiley & Sons, Ltd. Abstract : Laparoscopic as good as open